Tuberculosis as Public Health Problem in the Slovak Republic - Martin SAMOHYL; Ivan SOLOVIC; Jana SVECOVA; Roman RAMS; Katarina HIROSOVA; Jana JURKOVICOVA (Tehran University of Medical Sciences, 2017)
Tuberculosis as Public Health Problem in the Slovak Republic